2010
DOI: 10.1007/s10549-010-0974-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of aromatase inhibitors in the first-line treatment for hormone sensitive advanced or metastatic breast cancer

Abstract: To undertake a systematic review of three firstline treatments (letrozole, anastrozole and exemestane) for hormone sensitive advanced or metastatic breast cancer (MBC) in post-menopausal women. We searched six databases from inception up to January 2009 for relevant trials regardless of language or publication status. Randomised controlled clinical trials assessing the safety and efficacy of first-line AIs for post-menopausal women with hormone receptor-positive (HR?, i.e. ER? and/or PgR?) with or without ErbB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 45 publications
(79 reference statements)
2
51
0
1
Order By: Relevance
“…In terms of both PFS and OS, there are also advantages of treating patients with AIs compared to other ET, and letrozole seems to be the drug of choice [65,66] . The adverse effects observed using letrozole or anastrozole are similar than that observed with TAM, and the time-to-progression was better [67] . The combination anastrozole and fulvestrant in metastatic ER+ BC was superior to anastrozole alone [41] .…”
Section: Metastatic Breast Cancermentioning
confidence: 60%
See 1 more Smart Citation
“…In terms of both PFS and OS, there are also advantages of treating patients with AIs compared to other ET, and letrozole seems to be the drug of choice [65,66] . The adverse effects observed using letrozole or anastrozole are similar than that observed with TAM, and the time-to-progression was better [67] . The combination anastrozole and fulvestrant in metastatic ER+ BC was superior to anastrozole alone [41] .…”
Section: Metastatic Breast Cancermentioning
confidence: 60%
“…Most of the AEs is related to the estrogen deprivation [7] . According to a systematic review, TAM was associated with more serious AEs in comparison with AIs, while exemestane caused more frequently musculoskeletal symptoms and hot flushes, but in some trials no [67] . Another meta-analysis showed that patients treated with AIs had increased risk of gastrointestinal symptoms, such as nausea, vomiting and diarrhea, while the incidence of thromboembolic events and vaginal bleeding were decreased compared to other ETs [66] .…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Anastrozole seemed significantly superior to tamoxifen in terms of TTP in one trial (HR=1.42 (95% CI: 1.15, NR)), but not in the other (HR=1.01 (95% CI: 0.87, NR)). In terms of adverse events, no significant differences were found between letrozole and tamoxifen [48].…”
Section: Postmenopausalmentioning
confidence: 74%
“…A potential new therapeutic approach consists of suppressing oestrogen secretion with aromatase inhibitors, especially in post-menopausal women in whom the adrenal glands are the main source of oestrogens [143]. Letrozole is an aromatase inhibitor currently used to treat oestrogen receptor-positive breast cancer.…”
Section: Future Treatmentsmentioning
confidence: 99%